2017
DOI: 10.1371/journal.ppat.1006593
|View full text |Cite
|
Sign up to set email alerts
|

Nuclease escape elements protect messenger RNA against cleavage by multiple viral endonucleases

Abstract: During lytic Kaposi’s sarcoma-associated herpesvirus (KSHV) infection, the viral endonu- clease SOX promotes widespread degradation of cytoplasmic messenger RNA (mRNA). However, select mRNAs, including the transcript encoding interleukin-6 (IL-6), escape SOX-induced cleavage. IL-6 escape is mediated through a 3’ UTR RNA regulatory element that overrides the SOX targeting mechanism. Here, we reveal that this protective RNA element functions to broadly restrict cleavage by a range of homologous and non-homologou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 81 publications
(138 reference statements)
2
50
0
Order By: Relevance
“…This protective RNA element was termed SRE (for SOX resistance element), but we recently showed that the SRE is also effective against a broad range of viral endonucleases. Perhaps more surprisingly, the SRE is unable to restrict endonucleolytic cleavage originating from a cellular endonuclease, making it the first identified virus-specific RNase escape element (19). We showed that this broad-acting RNA element is not characterized by a defined sequence motif (19), rendering it difficult to identify new escaping transcripts by traditional sequence search.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…This protective RNA element was termed SRE (for SOX resistance element), but we recently showed that the SRE is also effective against a broad range of viral endonucleases. Perhaps more surprisingly, the SRE is unable to restrict endonucleolytic cleavage originating from a cellular endonuclease, making it the first identified virus-specific RNase escape element (19). We showed that this broad-acting RNA element is not characterized by a defined sequence motif (19), rendering it difficult to identify new escaping transcripts by traditional sequence search.…”
mentioning
confidence: 96%
“…Perhaps more surprisingly, the SRE is unable to restrict endonucleolytic cleavage originating from a cellular endonuclease, making it the first identified virus-specific RNase escape element (19). We showed that this broad-acting RNA element is not characterized by a defined sequence motif (19), rendering it difficult to identify new escaping transcripts by traditional sequence search. Consequently, the host versus viral endonuclease dichotomy is the only defining characteristic of this novel type of RNA element.…”
mentioning
confidence: 96%
See 3 more Smart Citations